Chalcogenide-containing compound, solid electrolyte, positive electrode material, dielectric, and battery

By developing a new choline compound, the composition of specific elements and halogen and one-dimensional octahedral and tetrahedral structures are used to solve the problem of poor thermal stability of existing battery materials in high temperature environments, and high thermal stability and good electrochemical properties are achieved.

JP2025059928APending Publication Date: 2025-04-10SUMITOMO CHEM CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023170336
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing battery materials have poor thermal stability in high temperature environments, making it difficult to meet the application needs in high temperature environments.

Method used

A new choline compound was developed, which consists of specific elements (such as rubidium, zinc, manganese, iron, etc.) and halogen (such as fluorine, chlorine, bromine, iodine, etc.), and has a crystal structure of one-dimensional octahedral and tetrahedral structures, and achieves high thermal stability through specific crystal structures and compositions.

Benefits of technology

The material maintains good thermal stability at high temperatures and is suitable for batteries and electronic equipment in high temperature environments, improving the thermal performance and electrochemical stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059928000001_ABST
    Figure 2025059928000001_ABST
Patent Text Reader

Abstract

To provide a compound having high heat resistance.SOLUTION: A compound is represented by the following formula (1): AxMyM2zCh4X (In the formula (1), A is at least one element selected from the group consisting of an alkali metal and Ag; M is at least one element selected from the group consisting of Zn, Mn, and Fe; Ch is at least one element selected from the group consisting of O, S, Se, and Te; M2 is a metal element other than A and M; and X is at least one element selected from the group consisting of F, Cl, Br, I, OH, SH, BF4, and BH4, where 3≤x≤5.5, 1.5≤y≤2.5, and 0≤z≤1.0.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to chalcogenide-containing compounds, solid electrolytes, cathode materials, dielectrics, and batteries. [Background technology]

[0002] In recent years, solid electrolytes have been attracting attention as electrolytes to be used in electrochemical devices such as lithium ion batteries (Patent Documents 1 and 2). Compared with conventional electrolytic solutions, solid electrolytes have superior high-temperature durability, high-voltage resistance, etc., and are therefore considered to be useful for improving battery performance such as safety, high capacity, rapid charge / discharge, and pack energy density. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2020 / 220697 [Patent Document 2] International Publication No. 2021 / 024785 Summary of the Invention [Problem to be solved by the invention]

[0004] Here, since batteries may need to operate in high-temperature environments, higher heat resistance is required for each component of the battery, such as electrolytes and electrodes. Similarly, heat resistance is also required for electronic devices such as capacitors. In view of these circumstances, there is a great demand for materials with higher heat resistance.

[0005] The present disclosure has been made in view of the above circumstances, and aims to provide a compound having high heat resistance, and also aims to provide a solid electrolyte, a positive electrode material, a dielectric, and a battery containing such a compound. [Means for solving the problem]

[0006] The present disclosure includes the following exemplary embodiments. [1] A compound represented by the following composition formula (1). A x M y M 2 z Ch4X···(1) (In formula (1), A is at least one element selected from the group consisting of alkali metals and Ag, M is at least one element selected from the group consisting of Zn, Mn, and Fe, Ch is at least one element selected from the group consisting of O, S, Se, and Te, and M 2 is a metal element other than A and M, and X is at least one selected from the group consisting of F, Cl, Br, I, OH, SH, BF4, and BH4, and 3≦x≦5.5, 1.5≦y≦2.5, and 0≦z≦1.0. [2] The crystal structure has a one-dimensional chain in which octahedral structures centered on alkali metal ions are connected, and a one-dimensional chain in which tetrahedral structures centered on metal ions are connected, The compound according to [1], wherein the one-dimensional chains in which the octahedral structures are linked and the one-dimensional chains in which the tetrahedral structures are linked are arranged alternately. [3] A compound of [1] or [2] having a tetragonal or rectangular crystal structure. [4] A compound according to any one of [1] to [3], having a crystal structure assigned to the space group I4mm, I4 / mmm, or P21ab. [5] A solid electrolyte comprising any one of the compounds of [1] to [4]. [6] A positive electrode material containing any one of the compounds [1] to [4]. [7] A dielectric material containing any one of the compounds [1] to [4]. [8] A battery containing any one of the compounds [1] to [4]. Effect of the Invention

[0007] According to the present disclosure, it is possible to provide a compound having high heat resistance, and also to provide a solid electrolyte, a positive electrode material, a dielectric, and a battery containing such a compound. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 shows the powder X-ray diffraction patterns of Examples 1 to 3. [Diagram 2] FIG. 2 shows the powder X-ray diffraction patterns of Examples 4 and 5. [Diagram 3] FIG. 3 is a diagram showing the crystal structure of the chalcogenide-containing compound of Example 1 as viewed from a direction perpendicular to the c-axis. [Figure 4] FIG. 4 is a diagram showing the crystal structure of the chalcogenide-containing compound of Example 1 as viewed along the a-axis. [Diagram 5] FIG. 5 is a diagram showing the crystal structure of the chalcogenide-containing compound of Example 1 as viewed along the c-axis. [Figure 6] FIG. 6 shows an Arrhenius plot obtained for the chalcogenide-containing material of Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The compound of this embodiment is a compound represented by the following composition formula (1) (hereinafter, also referred to as a chalcogenide-containing compound). A x M y M 2 z Ch4X···(1) (In formula (1), A is at least one element selected from the group consisting of alkali metals and Ag, M is at least one element selected from the group consisting of Zn, Mn, and Fe, Ch is at least one element selected from the group consisting of O, S, Se, and Te, and M 2is a metal element other than A and M, and X is at least one selected from the group consisting of F, Cl, Br, I, OH, SH, BF4, and BH4, and 3≦x≦5.5, 1.5≦y≦2.5, and 0≦z≦1.0.

[0010] A may contain at least one element selected from the group consisting of Li, Na, and Ag, and may contain at least one of Li and Na.

[0011] In the formula (1), x may be 3.5 to 5.5, may be 4 to 5.3, or may be 4.5 to 5.2.

[0012] M may contain at least one of Zn and Mn, and may contain Zn. M may contain a divalent element.

[0013] The value of y may be 1.6 to 2.4, or may be 1.7 to 2.3.

[0014] Ch may contain at least one element of O and S, and may contain S.

[0015] M 2 may contain a trivalent or higher metal element. 2 For example, the element may be at least one element selected from the group consisting of Ga, In, and Nb, and may be at least one of Ga and In.

[0016] z may be greater than 0 and equal to or less than 0.8, may be 0.01 to 0.5, may be 0.05 to 0.4, may be 0.1 to 0.3, or may be 0.1 to 0.25.

[0017] The solid (crystal) of the chalcogenide-containing compound of this embodiment may have a one-dimensional chain in which octahedral structures are connected around an alkali metal ion and a one-dimensional chain in which tetrahedral structures are connected around a metal ion in the crystal structure. The metal ion may be the metal ion M in formula (1). Here, the one-dimensional chain in which octahedral structures are connected refers to a structure in which octahedral structures are repeatedly arranged in a chain along a certain direction in the crystal. In addition, the one-dimensional chain in which tetrahedral structures are connected refers to a structure in which tetrahedral structures are repeatedly arranged in a chain along a certain direction in the crystal.

[0018] The one-dimensional chains of linked octahedral structures and the one-dimensional chains of linked tetrahedral structures may be arranged alternately in the crystal structure. Here, the alternating arrangement refers to a structure in which one-dimensional chains of linked octahedral structures and one-dimensional chains of linked tetrahedral structures are repeatedly arranged alternately along a certain direction in the crystal. In the crystal, the one-dimensional chains of linked octahedral structures and the one-dimensional chains of linked tetrahedral structures may be arranged alternately in two or more directions that are not parallel to each other.

[0019] In the one-dimensional chain, the octahedral structures may share vertices. That is, each octahedral structure in the one-dimensional chain may share one atom with each of the two octahedral structures adjacent to the octahedral structure. The shared atom may be an atom included in X in formula (1). Here, when the atom included in X is F, Cl, Br, or I, it refers to these atoms themselves, and when X is SH, OH, BH4, or BF4, S, O, or B is shared, respectively.

[0020] The tetrahedral structures in the one-dimensional chain may share edges. That is, each tetrahedral structure in the one-dimensional chain may share two atoms with each of the two tetrahedral structures adjacent to the tetrahedral structure. The shared atoms may be atoms included in Ch in formula (1).

[0021] The octahedral structure and the tetrahedral structure may share a vertex. The shared atom may be an atom included in Ch in formula (1). In this case, each octahedral structure included in the one-dimensional chain may share a vertex with a tetrahedral structure included in each one-dimensional chain in which four adjacent tetrahedral structures are connected. The tetrahedral structure may share a vertex with four adjacent octahedral structures.

[0022] In the crystal structure, the metal ion A in formula (1) may be contained in a gap surrounded by the tetrahedral structure and the octahedral structure, or may be contained both in the octahedral structure and in the gap.

[0023] The crystal of the chalcogenide-containing compound of this embodiment may have a tetragonal or orthorhombic crystal structure, and may have a crystal structure that belongs to the space group I4mm, I4 / mmm, or P21ab.

[0024] The method for producing the chalcogenide-containing compound of the present embodiment is not particularly limited, but may include a method of firing raw materials. 2 and X, for example, a chalcogenide compound of A, a chalcogenide compound of M, 2 and a salt containing A and X. The raw materials may be weighed so that the resulting chalcogenide compound has a desired composition, and may be mixed in a mortar or the like before firing. The raw materials may be weighed and mixed in an atmosphere containing an inert gas such as nitrogen (in an inert atmosphere). The firing temperature of the raw materials may be appropriately changed depending on the raw materials used, and may be, for example, 300 to 700°C, or 350 to 650°C. The firing may be performed on the raw materials contained in a degassed container (for example, a container formed of a heat-resistant material such as Pyrex (registered trademark)).

[0025] The chalcogenide-containing compound of the present embodiment can be used as a material for electrochemical devices such as capacitors and batteries. Examples of such materials include electrolytes (solid electrolytes) and positive electrode active materials. Examples of batteries include batteries that perform charging and discharging by moving alkali metal ions between a positive electrode and a negative electrode, such as lithium ion batteries and sodium ion batteries. The chalcogenide-containing compound of the present embodiment can be used as an electrode material such as a positive electrode active material or an ion conductor, and may be contained in at least one of the positive electrode and the negative electrode, or may be contained in the positive electrode. The chalcogenide-containing compound of the present embodiment can also be used as a dielectric.

[0026] The battery of this embodiment will be described below by taking a lithium ion battery as an example. The lithium ion battery includes a positive electrode, a negative electrode, and an electrolyte (solid electrolyte) disposed between the positive electrode and the negative electrode. The chalcogenide-containing compound of this embodiment may be included in the electrolyte or the positive electrode of the lithium ion battery. The positive electrode of the lithium ion battery is not particularly limited, and may contain a positive electrode active material and, as necessary, a conductive agent, a binder, and the like. The positive electrode may be a layer of a positive electrode material containing these materials formed on a current collector. The positive electrode active material may contain the chalcogenide-containing compound of this embodiment, but may also contain other materials, such as a lithium-containing composite metal oxide containing lithium (Li) and at least one transition metal selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, and Cu. Examples of such lithium composite metal oxides include LiCoO2, LiNiO2, LiMn2O4, Li2MnO3, LiNi x Mn y Co 1-x-y O2[0 <x+y<1])、LiNi x Co y Al 1-x-y O2[0 <x+y<1])、LiCr 0.5 Mn 0.5Examples of the positive electrode active material include O2, LiFePO4, Li2FeP2O7, LiMnPO4, LiFeBO3, Li3V2(PO4)3, Li2CuO2, Li2FeSiO4, and Li2MnSiO4. When the positive electrode active material contains an alkali metal element other than Li, specific examples thereof include those in which Li in the above specific examples is replaced with another alkali metal.

[0027] The negative electrode of the lithium ion battery is not particularly limited, and may contain a negative electrode active material and, if necessary, a conductive assistant, a binder, etc. Examples of the negative electrode include metals such as Li, Si, P, Sn, Si-Mn, Si-Co, Si-Ni, In, and Au, alloys containing these metals, carbon materials such as graphite, and materials in which lithium ions are inserted between layers of the carbon materials.

[0028] The material of the current collector is not particularly limited, and may be a simple metal or an alloy of metals such as Cu, Mg, Ti, Fe, Co, Ni, Zn, Al, Ge, In, Au, Pt, Ag, and Pd.

[0029] The electrolyte layer may have multiple layers. For example, in addition to the solid electrolyte layer containing the chalcogenide-containing compound of this embodiment, a sulfide solid electrolyte layer may be included. A sulfide solid electrolyte layer may be included between the solid electrolyte containing the chalcogenide-containing compound of this embodiment and the negative electrode. However, since the solid electrolyte layer containing the chalcogenide-containing compound of this embodiment has high electrochemical stability, even if it does not contain a sulfide solid electrolyte layer and is in direct contact with the negative electrode, a short circuit is unlikely to occur in the battery. The sulfide solid electrolyte is not particularly limited, but examples thereof include Li6PS5Cl, Li2S-PS5, Li 10 GeP2S 12 , Li 9.6 P3S 12 , Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3, Li3PS4, etc. When the solid electrolyte layer contains an alkali metal element other than Li, specific examples thereof include those in which Li in the above specific examples is replaced with another alkali metal.

[0030] When the chalcogenide-containing compound of the present embodiment is used as a dielectric, it can be used as a material for a wide variety of electronic devices, such as, for example, a resin for fingerprint authentication sensors, a resin for insulating materials for power, a resin for antenna materials, various capacitor materials, a capacitor material for a substrate with built-in passive elements, a dielectric filter, a vibration generator, a conversion sensor, an ignition device, a memory, a piezoelectric element, etc. The chalcogenide-containing compound of the present embodiment may be a ferroelectric. EXAMPLES

[0031] Example 1 A 5-x M 2-x M' x Ch4X (a chalcogenide-containing material) can be synthesized by solid-state ceramic synthesis. Na5Zn2S4Br is used as an example. Stoichiometric amounts of starting materials including Na2S, ZnS, and NaBr were weighed and mixed uniformly in a nitrogen-filled glove box using a mortar. Each raw material was weighed and mixed so that the weight of the target product obtained was 1 g. The mixture was then pressed into pellets and transferred to a Pyrex tube, which was degassed and sealed with a flame torch. The Pyrex tube was then heated to 550°C at a heating rate of 10°C / min, fired for 24 hours, and then naturally cooled to room temperature. The tube was then transferred to a glove box and the sample was collected.

[0032] [Examples 2 to 7] Other materials were synthesized in the same manner using the corresponding starting materials. That is, the chalcogenide-containing materials of each example were produced in the same manner as in Example 1, except that the firing temperature and the starting materials were used as shown in Table 1.

[0033] [Table 1]

[0034] Comparative Example 1 Ball mill In an argon atmosphere having a dew point of -70°C or less (hereinafter referred to as a dry argon atmosphere), 0.4381 g of LiCl and 0.7619 g of InCl3 were weighed out to prepare raw materials. The above raw materials were placed in a zirconia pot for a planetary ball mill described below, and 65 g of zirconia balls having a diameter of 5 mm were added. The mixture was treated for 30 minutes at 1200 rpm so as to cause a mechanochemical reaction, thereby obtaining a crude composition of Comparative Example 1. Planetary ball mill equipment: Emax manufactured by Verder Scientific Co., Ltd. ·annealing The crude composition of Comparative Example 1 obtained above was heated in a dry argon atmosphere at 230° C. for 5 hours to obtain a compound of Comparative Example 1 having a feed composition of Li3InCl6.

[0035] Comparative Example 2 Raw materials were prepared by weighing out 0.1364 g of Li2O and 1.0636 g of ZrCl4. The raw material was placed in a zirconia pot for the planetary ball mill, and 65 g of zirconia balls having a diameter of 5 mm were added. The mixture was treated for 120 minutes at 1200 rpm so as to cause a mechanochemical reaction, thereby obtaining the compound of Comparative Example 2.

[0036] <Powder X-ray diffraction measurement> The crystal structure of the obtained chalcogenide-containing compound was evaluated by powder X-ray diffraction measurement at 25°C. FIG. 1 shows the powder X-ray diffraction patterns of Examples 1 to 3. FIG. 2 shows the powder X-ray diffraction patterns of Examples 4 and 5. Table 2 shows the space group of each sample obtained by the X-ray diffraction measurement. The powder X-ray diffraction measurement was performed under the following measurement conditions. In order to prevent the sample from directly contacting the air, the measurement was performed after protecting the sample space with polyimide tape in a glove box. Measurement equipment: SmartLab (Rigaku Corporation) X-ray generator: CuKα source, voltage 40kV, current 50mA X-ray detector: Semiconductor detector Measurement range: Diffraction angle 2θ=5°~80° Scan speed: 2.5° / min Fig. 3 is a view of the crystal structure of the chalcogenide-containing compound of Example 1 viewed from a direction perpendicular to the c-axis. Fig. 4 is a view of the crystal structure of the chalcogenide-containing compound of Example 1 viewed from a direction along the a-axis. Fig. 5 is a view of the crystal structure of the chalcogenide-containing compound of Example 1 viewed from a direction along the c-axis.

[0037] <Evaluation of heat resistance in Examples 1 to 5, Comparative Example 1 and Comparative Example 2> A pressure molding die including a frame, a lower punch, and an upper punch was prepared. The frame was made of insulating polycarbonate. The upper punch and the lower punch were both made of electronically conductive stainless steel and were electrically connected to the terminals of an impedance analyzer (S11260 manufactured by Solatron Analytical).

[0038] Using the above pressure molding die, the ionic conductivity of the chalcogenide-containing compound was measured by the following method. First, in a dry argon atmosphere, the powder of the chalcogenide-containing compound was filled on the lower part of the punch inserted vertically from below into the hollow part of the frame mold. Then, the upper part of the punch was pressed into the hollow part of the frame mold from above, so that a pressure of 370 MPa was applied to the powder of the chalcogenide-containing compound inside the pressure molding die. After the pressure was applied, the punch was clamped from above and below with a jig to fix it, and while a constant pressure was maintained, the impedance of the chalcogenide-containing compound was measured by the electrochemical impedance measurement method using the above impedance analyzer.

[0039] A Cole-Cole diagram was created from the impedance measurement results. In the Cole-Cole diagram, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance was smallest was regarded as the resistance value to the ionic conduction of the chalcogenide-containing compound. Using this resistance value, the ionic conductivity was calculated based on the following formula (III). The ionic conductivity (σ 25℃ ) are shown in Table 2. σ = (R SE ×S / t) -1 (III) Where: σ is the ionic conductivity, S is the contact area of ​​the chalcogenide-containing compound with the top of the punch (equal to the cross-sectional area of ​​the hollow part of the mold); R SE is the resistance value of the chalcogenide-containing compound in an impedance measurement, t is the thickness of the chalcogenide-containing compound when pressure is applied.

[0040] Each sample in the pressure molding die was heated to 80°C, and the ionic conductivity (σ before After that, each sample was heated to 100°C and held at 100°C for 90 minutes. After cooling to 80°C, each sample was measured again at 80°C for ionic conductivity (σ after ) was measured. The rate of change in ionic conductivity was calculated from the measured ionic conductivity using the following formula. The rate of change is shown in Table 2. (Rate of change in ionic conductivity)=(σ after -σ before ) / σ before

[0041] Using the above method, ionic conductivity was measured at five temperatures (25°C, 40°C, 60°C, 80°C, and 100°C) within the temperature range of 25°C to 100°C. Figure 6 shows an Arrhenius plot obtained for the chalcogenide-containing material of Example 5. Ionic conductivity was measured at five points for both increasing and decreasing temperature. In Figure 6, the plots for increasing and decreasing temperature almost overlap.

[0042] <Evaluation of heat resistance in Examples 6 and 7, and Comparative Example 3> Using the above pressure molding die, the heat resistance of the chalcogenide-containing compound was evaluated by the following method. First, in a dry argon atmosphere, a powder of a chalcogenide-containing compound was filled into the hollow part of a frame mold above the lower part of a punch that was inserted vertically from below, and then the upper part of the punch was pressed into the hollow part of the frame mold from above, thereby applying a pressure of 370 MPa to the powder of the chalcogenide-containing compound inside the pressure molding die. Next, Li6PS5Cl powder was filled above and below the chalcogenide-containing compound so as to be in contact with the compound, and the punch was pressed again to apply a pressure of 370 MPa, thereby obtaining a laminate. As Comparative Example 3, a laminate was produced in the same manner as in Comparative Example 1 except that the chalcogenide-containing compound was used.

[0043] After pressure was applied, the punch was clamped from above and below with a jig to fix it in place, and while a constant pressure was maintained, the impedance of the laminate containing the chalcogenide-containing compound was measured by electrochemical impedance measurement using the impedance analyzer described above.

[0044] A Cole-Cole diagram was created from the impedance measurement results. In the Cole-Cole diagram, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance was smallest was regarded as the resistance value to the ionic conduction of the chalcogenide-containing compound. Using this resistance value, the ionic conductivity was calculated based on the following formula (III). The ionic conductivity (σ 25℃ ) are shown in Table 2. σ = (R SE ×S / t) -1 (III) Where: σ is the ionic conductivity, S is the contact area of ​​the laminate with the top of the punch (equal to the cross-sectional area of ​​the hollow part of the frame), R SE is the resistance value of the laminate in impedance measurement, t is the thickness of the laminate when pressure is applied.

[0045] Each sample in the above compression molding die was heated to 80 °C, and the ionic conductivity (σ before ) was measured. Then, each sample was once heated to 100 °C and held at 100 °C for 90 minutes. After each sample was cooled to 80 °C, the ionic conductivity (σ after ) at 80 °C was measured again at 80 °C. The change rate of the ionic conductivity was determined using the following formula from the measured ionic conductivity. The change rates are shown in Table 2. (Change rate of ionic conductivity) = (σ after - σ before ) / σ before

[0046]

Table 2

[0047] As shown in Table 2, for the chalcogenide-containing compounds of Examples 1 to 7, the change rate of the ionic conductivity was positive or, even if negative, its absolute value was smaller than those of Comparative Examples 1 and 2. From this, it can be said that the degree of deterioration due to heating is smaller than that of Comparative Examples 1 and 2, and the heat resistance is high.

[0048] <Calculation of the surface energy of the Li compound and evaluation of the calculation results> For the thermal stability evaluation of Li ions, the surface energy of each Li compound was determined using the density functional method. The surface energy is a quantity indicating the degree of destabilization from the bulk state when a crystal forms a surface, and is calculated by the following formula (nn). Surface energy = (E surf - n × E bulk ) ÷ S ··· (nn) Here, E surf is the total energy of the system calculated by the surface slab model, E bulk is the total energy of the system calculated by the unit cell model of the bulk crystal, S is the surface area of the surface slab model, and n is E surfThe surface energy is the number of atoms contained in a unit lattice divided by the number of atoms contained in the unit lattice. Surface energy reflects the instability of the surface of the material. Generally, if the surface energy of a system is high, the surface is unstable and the thermal stability of the surface is low, and the thermal stability of the interface is low when used as a solid electrolyte, cathode material, dielectric, or battery. The surface energies of the (001), (110), and (111) faces commonly observed in ordinary crystals were calculated, and the thermal stability was evaluated by taking the average value.

[0049] Although not wishing to limit the scope of the claims of this application, all density functional calculations shown in this application were performed using the computational chemistry software "Vienna ab initio simulation package (VASP)" provided by the University of Vienna, Republic of Austria, which is widely used and known to those skilled in the art. PBE was used as the density functional, and the slab model used in the calculation was created so that the axial lengths of the two axes in the direction of the surface extension were at least 10 Å, the thickness of the slab model was at least 10 Å, the number of atoms of each element contained in the system was an integer multiple of the unit crystal, and the thickness of the vacuum layer was 20 Å.

[0050] Example 1 The surface energy of Na5Zn2S4Br was calculated using the above method to evaluate its thermal stability. The bulk crystal structure used in the calculation was obtained by optimizing the experimental structure. The results are shown in Table 3 below.

[0051] Example 2 Na 4.8 Zinc 1.8 Ga 0.2 The surface energy of S4Br was calculated by the above method to evaluate its thermal stability. The bulk crystal structure used in the calculation was a supercell Na 40 Zinc 16 S 32 Create Br8, replace three Zn atoms with Ga, and delete one Na atom adjacent to each of the replaced Zn atoms, for a total of three. 77 Ga3Zn29 S 64 Br 16 By doing so, Na 4.8 Zinc 1.8 Ga 0.2 A structure with a composition ratio close to that of S4Br was obtained. This structure was optimized to obtain the bulk crystal structure. The results are shown in Table 3 below.

[0052] Example 3 Na 4.8 Zinc 1.8 In 0.2 The surface energy of S4Br was calculated by the above method to evaluate its thermal stability. The bulk crystal structure used in the calculation was obtained by substituting Ga with In in the structure of Example 2, and the surface energy of S4Br was calculated by the above method to evaluate its thermal stability. 77 In3Zn 29 S 64 Br 16 By doing so, Na 4.8 Zinc 1.8 In 0.2 A structure with a composition ratio close to that of S4Br was obtained. This structure was optimized to obtain the bulk crystal structure. The results are shown in Table 3 below.

[0053] Example 4 The surface energy of Na5Zn2S4SH was calculated using the above method to evaluate its thermal stability. The bulk crystal structure used in the calculation was obtained by optimizing the structure obtained by experiment. This was then optimized to obtain the bulk crystal structure. The results are shown in Table 3 below.

[0054] Example 5 Na 4.8 Zinc 1.8 In 0.2 The surface energy of S4SH was calculated by the above method to evaluate its thermal stability. The bulk crystal structure used in the calculation was the supercell Na 40 Zinc 16 S 32 (SH)8 is created, three Zn atoms are replaced with In, and one Na atom adjacent to each replaced Zn atom is deleted to create Na 77 Ga3Zn 29 S 64Br 16 By doing so, Na 4.8 Zinc 1.8 Ga 0.2 A structure with a composition ratio close to that of S4Br was obtained. This structure was optimized to obtain the bulk crystal structure. The results are shown in Table 3 below.

[0055] [Examples 10 to 14] The surface energy of the Li bodies in which Na was replaced with Li in Examples 1 to 5 was calculated by the above method, and the thermal stability was evaluated. Na was replaced with Li, and the structure was optimized to obtain the bulk crystal structure. The results are shown in Table 3 below.

[0056] [Comparative Examples 4 and 5] The surface energy was calculated by the above method for Li3ClO and LiBH4, which are known as solid electrolytes, and their thermal stability was evaluated. The structure files for these structures were obtained from the Materials Project, and the structures were optimized to obtain the bulk crystal structures. The results are shown in Table 3 below.

[0057] [Table 3]

[0058] As shown in Table 3 above, each of the compounds in Examples 1 to 5 and 10 to 14 has an average surface energy of 1.5 J / m 2 The comparative compound, which is experimentally known to have low thermal stability, has a surface energy of 2.0 J / m 2 This indicates that the compounds of Examples 1 to 5 and 10 to 14 have high thermal stability.

Claims

1. A compound represented by the following composition formula (1). A x M y M 2 z Ch 4 X・・・(1) (In formula (1), A is at least one element selected from the group consisting of alkali metals and Ag, M is at least one element selected from the group consisting of Zn, Mn, and Fe, Ch is at least one element selected from the group consisting of O, S, Se, and Te, and M 2 is a metal element other than A and M, and X is F, Cl, Br, I, OH, SH, BF 4 , and BH 4 At least one selected from the group consisting of: 3≦x≦5.5, 1.5≦y≦2.5, and 0≦z≦1.

0.

2. The crystal structure has a one-dimensional chain in which octahedral structures centered on alkali metal ions are connected, and a one-dimensional chain in which tetrahedral structures centered on metal ions are connected, The compound according to claim 1 , wherein the one-dimensional chains of linked octahedral structures and the one-dimensional chains of linked tetrahedral structures are arranged alternately.

3. 3. The compound according to claim 1 or 2, having a tetragonal or orthorhombic crystal structure.

4. Space group is I4mm, I4 / mmm or P2 1 The compound according to claim 1 or 2, having a crystal structure assigned to ab.

5. A solid electrolyte comprising the compound according to claim 1 or 2.

6. A positive electrode material containing the compound according to claim 1 or 2.

7. A dielectric material comprising the compound according to claim 1 or 2.

8. A battery containing a compound according to claim 1 or 2.

Citation Information

Patent Citations

  • Solid electrolyte material for lithium secondary battery, electrode, and battery

    WO2020220697A1

  • Solid electrolyte, solid electrolyte layer, and solid electrolyte cell

    WO2021024785A1